NEW DATA ON FAUNA AND BIOSTRATIGRAPHY ON NORIAN DEPOSITS IN THE KOTEL'NYI ISLAND (NEW SIBERIAN ISLANDS) - Konstantinov A.G.; Sobolev E.S.; Klets T.V. (My University, 2003)
A section of lower and middle Norian deposits in the Tikhaya River lower courses of (the central part of Kotel’nyi Island, New Siberian Islands) is described. After revision, the taxonomic composition of fauna from the sequence is verified, and formerly unknown taxa are identified. Stratigraphic range of ammonoids, nautiloids, coleoids, and conodonts in the section are analyzed, and the local biostratigraphic scheme, which includes zones, subzones, and beds with fauna, is suggested for the lower-middle Norian interval. Distinguished for the first time are beds with nautiloids, the Striatosirenites kinasovi Zone, and Cyrtopleurites ex gr. altissimus Beds with ammonoids. The local biostratigraphic scheme of Norian deposits is correlated with the ammonoid zonation in Canada and with the standard scale. Ammonoids of the genus Cyrtopleurites , which have been found for the first time in deposits of the Kotel’nyi Island and are characteristic of the Cyrtopleurites bicrenatus Zone, the lower one in the middle Norian of the standard scale, enabled the direct Boreal-Tethyan correlation of their host rocks and positioning of the lower-middle Norian boundary in Boreal regions. Geographic ranges of ammonoid, nautiloid, coleoid, and conodont taxa from Norian deposits of the Kotel’nyi Island are considered. Based on peculiar features of the studied fauna (coexistence of Boreal and Tethyan elements, a significant proportion of cosmopolitan taxa, and presence of species known from North America), the Kotel’nyi island region is defined as a separate subprovince in the Siberian Province of the Boreal Realm.
Keywords: Norian; Mesozoic::Triassic::Upper::Norian; Мезозой::Триасовая::Верхний::Норийский